Antimicrobial peptides effectively kill a broad spectrum of Listeria monocytogenes and Staphylococcus aureus strains independently of origin, sub-type, or virulence factor expression - Gottlieb, Caroline Trebbien (BioMed Central, 2008)
BACKGROUND: Host defense peptides (HDPs), or antimicrobial peptides (AMPs), are important components of the innate immune system that bacterial pathogens must overcome to establish an infection and HDPs have been suggested as novel antimicrobial therapeutics in treatment of infectious diseases. Hence it is important to determine the natural variation in susceptibility to HDPs to ensure a successful use in clinical treatment regimes. RESULTS: Strains of two human bacterial pathogens, Listeria monocytogenes and Staphylococcus aureus, were selected to cover a wide range of origin, sub-type, and phenotypic behavior. Strains within each species were equally sensitive to HDPs and oxidative stress representing important components of the innate immune defense system. Four non-human peptides (protamine, plectasin, novicidin, and novispirin G10) were similar in activity profile (MIC value spectrum) to the human β-defensin 3 (HBD-3). All strains were inhibited by concentrations of hydrogen peroxide between 0.1% – 1.0%. Sub-selections of both species differed in expression of several virulence-related factors and in their ability to survive in human whole blood and kill the nematode virulence model Caenorhabditis elegans. For L. monocytogenes, proliferation in whole blood was paralleled by high invasion in Caco-2 cells and fast killing of C. elegans, however, no such pattern in phenotypic behavior was observed for S. aureus and none of the phenotypic differences were correlated to sensitivity to HDPs. CONCLUSION: Strains of L. monocytogenes and S. aureus were within each species equally sensitive to a range of HDPs despite variations in subtype, origin, and phenotypic behavior. Our results suggest that therapeutic use of HDPs will not be hampered by occurrence of naturally tolerant strains of the two species investigated in the present study.